Beginning SharePoint 2013 development - Fox, Steven, 1970- (Wrox programmer to programmer, 2013)
A complete revision to a popular SharePoint developer's resource Fully updated for SharePoint 2013, this book is an ideal starting place for SharePoint development. Covering all the major topics that a new developer needs to know in order to get started, this resource contains 100 percent new content and addresses the major overhaul to the SharePoint 2013 platform. The team of authors, led by Microsoft's Steve Fox, presents you with a detailed overview that helps you establish a starting point for development. They then walk you through ways to advance your knowledge so that you le.